Characteristics and oil sorption effectiveness of areca nut husk / Nik Khairul Irfan Nik Ab Lah ... [et al.] - Nik Ab Lah, Nik Khairul Irfan; James Ketek, Jacquinn Alizcia; Tengku Mohd, Tengku Amran (Universiti Teknologi MARA, 2021)
Oil spill accident occur due to human carelessness and error during oil transportation, storage, and production of the hydrocarbon. Effect of oil spill can be either short or long term. It is not only affecting the environment but also marine life, economy, and social. Thus, effective recovery and control method must be carefully implemented to minimise the effect. There are various studies and technologies to mitigate the oil spill incident but mostly the techniques are very expensive, difficult and use of non-environmental friendly material. Hence, this study is conducted to study areca nut husk as a potential oil adsorbent for oil spill recovery. The characteristics of areca nut husk include morphological structures and chemical composition. The areca nut husk oil sorption effectiveness and capacity also been investigated. Areca nut husk were tested for both heavy crude oil and diesel adsorption. The result shows that the efficiency of oil sorption of areca nut husk toward heavy crude oil is 14.8% and it can be an alternative sorbent material to the current modern material. Meanwhile, the areca nut husk is not recommended to be used for diesel absorption activity for its low effectiveness (i.e., 2.04%) showed in this study.